2012
DOI: 10.1103/physrevb.85.155301
|View full text |Cite
|
Sign up to set email alerts
|

Fermi level tuning and a large activation gap achieved in the topological insulator Bi2Te2Se by Sn doping

Abstract: We report the effect of Sn doping on the transport properties of the topological insulator Bi 2 Te 2 Se studied in a series of Bi 2−x Sn x Te 2 Se crystals with 0 x 0.02. The undoped stoichiometric compound (x = 0) shows an n-type metallic behavior with its Fermi level pinned to the conduction band. In the doped compound, it is found that Sn acts as an acceptor and leads to a downshift of the Fermi level. For x 0.004, the Fermi level is lowered into the bulk forbidden gap and the crystals present a resistivity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
133
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(148 citation statements)
references
References 43 publications
12
133
0
Order By: Relevance
“…[14,[18][19][20][21][22][23][24][25][26][27][28][29]. On the other hand, in the bulk limit shown in (g) at t = 1000 nm, Δ(t) is zero over most of the range of N BD and n SD .…”
Section: Resultsmentioning
confidence: 95%
“…[14,[18][19][20][21][22][23][24][25][26][27][28][29]. On the other hand, in the bulk limit shown in (g) at t = 1000 nm, Δ(t) is zero over most of the range of N BD and n SD .…”
Section: Resultsmentioning
confidence: 95%
“…At very low concentrations, this state would be relatively localized, and would pin the Fermi energy to the gap, acting as a carrier concentration buffer, much like Sn does in Sn:Bi 2 Te 2 Se. [37][38][39] V. CONCLUSION Our study of a broad range of compositions in the superconducting Sn 1−x In x Te system shows that Indium doped SnTe cannot be thought of as a simple hole doped semiconductor over its full superconducting composition range. The nature of the superconductivity and the carrier type change as a function of Indium doping, going from overall p-type to overall n-type and from a weakly coupled to a strongly coupled superconductor.…”
Section: Electronic Structurementioning
confidence: 99%
“…The second route to improve the insulating property of Bi 2 Te 2 Se is to employ Sn doping to the Bi site. 109) Using both routes, it has been shown to be possible to achieve surface-dominated transport in bulk single crystals. 108,109) The discovery of tetradymite TI materials demonstrated that elucidating the parity eigenvalues based on ab initio band calculations is a practical and powerful strategy for making predictions for new TI materials.…”
Section: Three-dimensional Tismentioning
confidence: 99%
“…109) Using both routes, it has been shown to be possible to achieve surface-dominated transport in bulk single crystals. 108,109) The discovery of tetradymite TI materials demonstrated that elucidating the parity eigenvalues based on ab initio band calculations is a practical and powerful strategy for making predictions for new TI materials. In fact, the next TI material discovered after Bi 2 Se 3 and Bi 2 Te 3 was TlBiSe 2 , and its discovery, [110][111][112] done in 2010, was also led by theoretical predictions.…”
Section: Three-dimensional Tismentioning
confidence: 99%
See 1 more Smart Citation